2023
DOI: 10.1021/acs.energyfuels.3c01971
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effect on Undrained Mechanical Properties of Hydrate-Bearing Clayey Silts in the South China Sea

Abstract: Nearly 90% of hydrate resources are found in low-permeability and fine-grained soils, which requires investigation on the undrained mechanical characteristics of hydrate-bearing fine-grained soils (HBFGSs) to accomplish safe and efficient hydrate exploitation. Additionally, factors such as hydrothermal and geothermal gradients of the marine sediments and hydrate extraction by heat injection method simultaneously require an understanding of the temperature effect on the stability of HBFGSs and overburden hydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Numerous scholars from various fields have conducted extensive research on the mechanical characteristics of NGH layers. Research has shown that factors such as hydrate saturation, effective stress, particle size distribution, strain rate, and temperature–pressure conditions all exert impacts on the mechanical characteristics of NGH reservoirs. The higher the hydrate saturation, the greater the strength and modulus of NGH reservoirs, especially when hydrate saturation exceeds 50% . With an increase in effective stress, NGH reservoirs’ strength and stiffness undergo a significant increase, accompanied by a transition from strain-softening behavior to strain-hardening behavior; Miyazaki et al confirmed that hydrate-bearing sediments exhibited greater strength at higher strain rates .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous scholars from various fields have conducted extensive research on the mechanical characteristics of NGH layers. Research has shown that factors such as hydrate saturation, effective stress, particle size distribution, strain rate, and temperature–pressure conditions all exert impacts on the mechanical characteristics of NGH reservoirs. The higher the hydrate saturation, the greater the strength and modulus of NGH reservoirs, especially when hydrate saturation exceeds 50% . With an increase in effective stress, NGH reservoirs’ strength and stiffness undergo a significant increase, accompanied by a transition from strain-softening behavior to strain-hardening behavior; Miyazaki et al confirmed that hydrate-bearing sediments exhibited greater strength at higher strain rates .…”
Section: Introductionmentioning
confidence: 99%